Kinematic analysis of the X4 translational–rotational parallel robot. (2nd October 2018) - Staicu, Stefan; Shao, Zhufeng; Zhang, Zhaokun; Tang, Xiaoqiang; Wang, Liping
High-speed pick-and-place parallel manipulators have attracted considerable academic and industrial attention because of their numerous commercial applications. The X4 parallel robot was recently presented at Tsinghua University. This robot is a four-degree-of-freedom spatial parallel manipulator that consists of high-speed closed kinematic chains. Each of its limbs comprises an active pendulum and a passive parallelogram, which are connected to the end effector with other revolute joints. Kinematic issues of the X4 parallel robot, such as degree of freedom analysis, inverse kinematics, and singularity locus, are investigated in this study. Recursive matrix relations of kinematics are established, and expressions that determine the position, velocity, and acceleration of each robot element are developed. Finally, kinematic simulations of actuators and passive joints are conducted. The analysis and modeling methods illustrated in this study can be further applied to the kinematics research of other parallel mechanisms.